The significance of duty-free sales on board ferries to the transnational transport system in the Baltic Sea Region - Lindström, Bjarne; Palmer, Richard; Lång, Stefan; Ålands statistik- och utredningsbyrå (ÅSUB rapport, ISSN 1455-1977, 2011)
Svensk sammanfattning.
Keywords: tax-free-myynti; verovapaus; myynti; laivaliikenne; meriliikenne; autolautat; risteilyalukset; Itämeren alue